Phytoplankton physiology and functional traits under artificial upwelling with varying Si:N - Ortiz, Joaquin; Arístegui, Javier; Goldenberg, Silvan Urs; Fernández-Méndez, Mar; Taucher, Jan; Archer, Stephen D.; Baumann, Moritz; Riebesell, Ulf (Frontiers in Marine Science, 2024)
Artificial upwelling has been discussed as a nature-based solution to fertilize currently unproductive areas of the ocean to enhance food web productivity and atmospheric CO2 sequestration. The efficacy of this approach may be closely tied to the nutrient stoichiometry of the upwelled water, as Si-rich water upwelling should benefit the growth of diatoms, who are key players for primary production, carbon export and food web efficiency. With a mesocosm experiment in subtropical waters, we assessed the physiological and functional responses of an oligotrophic phytoplankton community to artificial upwelling under varying Si:N ratios (0.07-1.33). Deep water fertilization led to strongly enhanced primary productivity rates and net autotrophy across Si scenarios. At the community level, Si-rich upwelling temporarily increased primary production and consistently enhanced diatom growth, producing up to 10-fold higher abundances compared to Si-deficient upwelling. At the organism level, contrasting effects were observed. On the one hand, silicification and size of diatom cells remained unaffected by Si:N, which is surprising given the direct dependency of these traits on Si. On the other hand, diatom Chlorophyll a density and carbon density were strongly reduced and particulate matter C:N was elevated under Si-rich upwelling. This suggests a reduced nutritional value for higher trophic levels under high Si:N ratios. Despite these strong qualitative changes under high Si, diatom cells appeared healthy and showed high photosynthetic efficiency. Our findings reveal great physiological plasticity and adaptability in phytoplankton under artificial upwelling, with Si-dependent trade-offs between primary producer quantity and quality.